Antarctic Slope Current Modulates Ocean Heat Intrusions Towards Totten Glacier. Issue 17 (30th August 2021) - Nakayama, Yoshihiro; Greene, Chad A.; Paolo, Fernando S.; Mensah, Vigan; Zhang, Hong; Kashiwase, Haruhiko; Simizu, Daisuke; Greenbaum, Jamin S.; Blankenship, Donald D.; Abe‐Ouchi, Ayako; Aoki, Shigeru
Abstract: The Totten ice shelf (TIS) in East Antarctica has received increasing attention in recent years due to high basal melt rates, which have been linked to a presence of warm modified Circumpolar Deep Water (mCDW) observed at the ice front. We show that mCDW on‐shelf intrusions towards the TIS strengthen when the Antarctic Slope Current (ASC) weakens. This demonstrates that the ASC has a blocking effect and ASC weakening leads to on‐shelf intrusions, as proposed by previous observational studies. The interannual variability of the ASC is controlled primarily by atmospheric and oceanic conditions beyond our regional model domain. We further show that heat intrusions onto the continental shelf off the TIS are not influenced by off‐shelf warming but are enhanced with coastal freshening, suggesting positive feedback whereby ice melt and freshening upstream could start a chain reaction, leading to increased melt, and further coastal freshening. Plain Language Summary: East Antarctica's Totten Glacier holds enough ice to raise global sea levels by more than 4 m, and it has recently been melting at an alarming rate. To understand what causes high melt rates at the base of Totten's floating ice shelf, we developed an ocean model that shows how warm water masses circulate throughout the region. We find that the westward‐moving Antarctic Slope Current (ASC) has the ability to block warm water from flowing toward the Totten ice shelf. The warm ocean heat intrusions towards the Totten ice shelf are simulated in 1993–1994, 2004–2006, and 2015–2016 together with extreme ASC weakening events. The ASC strength in the interannual time scale, which caused these weakening events, is controlled primarily by atmospheric and oceanic processes that originate more than 1, 000 km away. We also find that as upstream ocean freshens, the blocking effect of the slope current could weaken, setting up a feedback mechanism in which a weaker slope current and on‐shelf freshening allows more warm water to access Totten, leading to increased melt, more on‐shelf intrusions of warm water, and yet more melt, ad infinitum. Key Points: On‐shelf intrusions of ocean heat peak when the Antarctic Slope Current (ASC) weakens Synoptic scale ocean circulation dominantly controls the interannual variability of ASC strength Heat intrusions towards the Totten ice shelf are enhanced with upstream coastal freshening